Proceedings of the 9th Annual SIGCSE Conference on Innovation and Technology in Computer Science Education 2004
DOI: 10.1145/1007996.1008020
|View full text |Cite
|
Sign up to set email alerts
|

Do senior CS students capitalize on recursion?

Abstract: CS students learn and practice recursion in CS1, Data-Structures, Introduction-to-Algorithms, and additional courses throughout the curriculum. Previous studies revealed difficulties of CS1 students with the concept and the construct of recursion. What about advanced students? They may well understand the concept and the construct of recursion; but do they invoke and utilize recursion as a problem solving means? The paper examines this aspect, with senior CS students. The students were given three algorithmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Other research envisaged involves studying how more senior computer science students cope with recursion in line with the work done by Ginat (2004) who showed that senior students do not always produce recursive solutions even when those would be the most appropriate solutions.…”
Section: Future Workmentioning
confidence: 99%
“…Other research envisaged involves studying how more senior computer science students cope with recursion in line with the work done by Ginat (2004) who showed that senior students do not always produce recursive solutions even when those would be the most appropriate solutions.…”
Section: Future Workmentioning
confidence: 99%
“…It is well known that the number of inversions in a permutation can be obtained by a merge sort (Ginat, 2004). We use a similar strategy to compute the d i while performing a merge sort on y 1 , .…”
Section: Fast Computation Of D I Where Dmentioning
confidence: 99%
“…Wherever programming is featured in introductory courses, recursion is usually avoided, even though it is present in mathematics courses, usually in the guise of numerical progressions, Euclid's algorithm, Newton-Raphson approximation method, and proofs by mathematical induction (Buck, 1963). Therefore, because university students often experience significant difficulties in grasping recursive programming (Sooriamurthi, 2001, Ginat, 2004, some educators have insisted on a better articulation between secondary and post-secondary curriculums. For instance, some researchers have been promoting a greater presence of discrete mathematics and proof techniques in secondary schools (Abramovich and Pieper, 1996, da Rosa, 2002, Rosenstein et al, 1997, Kaiser, 2004a, as well as the creation of computing clubs with activities about recursion (Gunion et al, 2009a).…”
Section: Curricular Approachesmentioning
confidence: 99%